POAC-Based Communication Governance of Islamic Religious Extension in Multiethnic Urban Asahan - Faisal Fahmi Rambe; Abdurrahman Abdurrahman; Fatkhur Rohman (Jurnal IPTEK Bagi Masyarakat, 2026)
This study examines the communication governance of Islamic religious extension in multiethnic urban communities in Asahan Regency using the POAC framework. A qualitative case study was conducted with seven informants, including Islamic religious extension officers, Ministry of Religious Affairs officials, religious leaders, and community members from different ethnic backgrounds. Data were collected through semi-structured interviews, participatory observation, and documentation, then analyzed thematically. The findings show that planning involved adaptive audience mapping, issue-based message selection, and multichannel media use, although written communication plans remained limited. Organizing was reflected in coordination among extension officers and collaboration with religious leaders, educational institutions, and local government. Actuating combined interpersonal, group, and digital communication to reach diverse audiences. Controlling was the weakest function because evaluation still relied mainly on activity reports and informal feedback rather than standardized indicators. This study positions religious extension officers as communication managers, not merely message transmitters. It recommends a more structured, documented, and evaluative communication governance system for Islamic religious extension in multiethnic urban communities.